HUBUNGAN BODY IMAGE DENGAN PERILAKU DIET PADA MAHASISWI FAKULTAS EKONOMI UNIVERSITAS NEGERI MANADO - Kristin S. Manongko; Tellma M. Tiwa; Sinta E. Kaunang (PSIKOPEDIA, 2022)
Diet is a plan or arrangement of eating and drinking patterns that aim to lose weight or maintain health. One of the factors that influence dietary behavior is a person's personality factor which is related to self-confidence about his body shape. The discrepancy between the ideal image and self-perception can cause a negative body image. If a person feels insecure about his body condition, he will go on a diet to get the ideal body. This research uses quantitative methods. This study aims to determine the relationship between Body Image and Dietary Behavior in students of the Faculty of Economics, Manado State University using 32 research samples. The data technique used in finding relationships and proving the relationship regarding the proposed hypothesis is a correlation test processed using IBM SPSS version 25 for Windows with a significance value (sig) of 0.744 greater than > 0.05 probability, so it can be concluded that there is no relationship between body image and dietary behavior.